EVOLUTION OF NANOTECH ASSISTED PCR DIAGNOSIS OF MYCOBACTERIUM TUBERCULOSIS AND ITS ASSESSMENT WITH CONVENTIONAL METHODS - Sawant, Deepak V.; Desai, M. M.; Patil, R. S.; Pawar, S. H. (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: This study was focused on assessment and performance of conventional and nanotech assisted methods for detection of Mycobacterium tuberculosis. Tuberculosis (TB) still leftovers one of the top ten causes of death worldwide, thus this study has undertaken the use of MNP for early detection of TB. Methods: A cross-sectional studies were conducted on clinical and radiological suspected TB patients in the department of microbiology at D. Y. Patil hospital Kolhapur. All samples received in the month of August 2016 to January 2017. Total One hundred twenty-sputum samples were processed for diagnosis of TB by ZN stain, culture on L. J. Medium and real-timePCR tests. Results: In our present study, 60.83% (73) patient male and 39.17 % (47) were female patient, showing a borderline male prevalence found in our study. Eighteen percent patients were found to be in the age group (21-30 y) are mostly affected for pulmonary tuberculosis. A significant difference was seen in the percentage of differentDNA extraction methods, the fig. being conventional chloroform-phenol 66.66%, the commercial kit 80%, magnetic bead 86.66% and MNPs method 99.66% found to be significant (P<0.0001**). Conclusion: In the present study the MNP-DNA extraction techniques with NALC followed by IS6110 target amplification were found superior for diagnosis of TB. The MNP assisted extraction method showed better results in terms of quantification and sensitivity of TB PCR diagnosis, evolving nanotech assisted innovative method.